COMMENT LA SCIENCE AGROÉCOLOGIQUE A ÉTÉ INTÉGRÉE DANS LE DROIT ET LA POLITIQUE AGRICOLES - Luc BODIGUEL, (Journal international de bioéthique et d'éthique des sciences, 2023)
Agroecology has become a trendy word in political and media discourse and the subject of international debates, but its meaning remains unclear. This article defines this experimental science and explains its substance, and then goes on to examine how and to what extent agricultural law has allowed it to enter the political arena. It explains why agricultural Frenc Law and UE agricuktural Policy struggles to offer a secure and comprehensive framework for agroecology whereas this multi-disciplinary, complex and systematic science is looking to the future and aims to protect future generations.